Testing a Low Molecular Mass Fraction of a Mushroom (Lentinus edodes) Extract Formulated as an Oral Rinse in a Cohort of Volunteers. (8th September 2011) - Signoretto, Caterina; Burlacchini, Gloria; Marchi, Anna; Grillenzoni, Marcello; Cavalleri, Giacomo; Ciric, Lena; Lingström, Peter; Pezzati, Elisabetta; Daglia, Maria; Zaura, Egija; Pratten, Jonathan; Spratt, David A.; et al.
Abstract : Although foods are considered enhancing factors for dental caries and periodontitis, laboratory researches indicate that several foods and beverages contain components endowed with antimicrobial and antiplaque activities. A low molecular mass (LMM) fraction of an aqueous mushroom extract has been found to exert these activities in in vitro experiments against potential oral pathogens. We therefore conducted a clinical trial in which we tested an LMM fraction of shiitake mushroom extract formulated in a mouthrinse in 30 young volunteers, comparing the results with those obtained in two identical cohorts, one of which received water (placebo) and the other Listerine. Plaque index, gingival index and bacterial counts in plaque samples were determined in all volunteers over the 11 days of the clinical trial. Statistically significant differences (P < 0.05 ) were obtained for the plaque index on day 12 in subjects treated with mushroom versus placebo, while for the gingival index significant differences were found for both mushroom versus placebo and mushroom versus Listerine. Decreases in total bacterial counts and in counts of specific oral pathogens were observed for both mushroom extract and Listerine in comparison with placebo. The data suggest that a mushroom extract may prove beneficial in controlling dental caries and/or gingivitis/periodontitis.